2017
DOI: 10.1055/s-0037-1602245
|View full text |Cite
|
Sign up to set email alerts
|

Fascia Lata Free Flap Anastomosed to the Superior Trochlear System for Reconstruction of the Anterior Skull Base

Abstract: This study aims to introduce a novel technique for the reconstruction of the anterior skull base using a free vascularized anterolateral thigh fascia lata free flap (FLFF) anastomosed to the superior trochlear artery (STA). The diameter of the STA was measured in 38 (76 sides) computed tomography angiographies (CTAs). Independently, six cadaver heads were used to measure the diameter of the supratrochlear system, and the model was applied to one of them. In women, the average diameter of the STA was 2.5 and 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…In perhaps the most novel approach, Reyes et al described the ability to achieve tension-free anastomosis with a 7-cm flap pedicle and the supratrochlear artery via a Lynch incision in a cadaver. 13 However, the authors note that since this is a cadaver study, cosmetic sequelae of a radix osteotomy cannot be assessed, and closure of the osteotomy could potentially compromise the flap pedicle. 13 Of note, none of the case reports in this review describe the use of vein grafts.…”
Section: Vessel Optionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In perhaps the most novel approach, Reyes et al described the ability to achieve tension-free anastomosis with a 7-cm flap pedicle and the supratrochlear artery via a Lynch incision in a cadaver. 13 However, the authors note that since this is a cadaver study, cosmetic sequelae of a radix osteotomy cannot be assessed, and closure of the osteotomy could potentially compromise the flap pedicle. 13 Of note, none of the case reports in this review describe the use of vein grafts.…”
Section: Vessel Optionsmentioning
confidence: 99%
“…13 However, the authors note that since this is a cadaver study, cosmetic sequelae of a radix osteotomy cannot be assessed, and closure of the osteotomy could potentially compromise the flap pedicle. 13 Of note, none of the case reports in this review describe the use of vein grafts. While vein grafts can significantly increase the length of a flap pedicle, allowing a flap to reach its recipient position while still being anastomosed in the neck, they do introduce additional risk in an already complex reconstruction.…”
Section: Vessel Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their small case series, there were 5 pedicled, 2 hybridized, and 2 free flap reconstructions with 100% flap survival [19] . Other myocutaneous regional flaps including the latissimus dorsi, trapezius, and pectoralis major have been previously cited for skull base reconstruction [3,22] . However, these regional flaps may not be ideal choices for ASB defects due to difficulty in transposing the flap above the inferior orbital rim and zygomatic arch.…”
Section: Locoregionalmentioning
confidence: 99%
“…CSF leak is the most common complication after reconstructive skull base surgery but other complications, such as meningitis, pneumocephalus, wound dehiscence, and stroke, can also occur [7,31] . In a large retrospective comparison study, Neligan et al [22] demonstrated that the overall complication rate was 33.5% in free flaps, 38.8% in local flaps, and 75% in pedicled flaps. The authors also reported compromised wound healing in 36.3% of pedicled flaps compared to only 10% of free flaps [22] .…”
Section: Complicationsmentioning
confidence: 99%